Progression from papilloma to carcinoma is accompanied by changes in antibody response to papillomavirus proteins. - Lin, Y L (1993)
Cottontail rabbit papillomavirus induces benign tumors, papillomas, in rabbits which progress at a high frequency to malignant tumors, carcinomas. Cottontail rabbit papillomavirus therefore provides an experimental model for oncogenic human papillomaviruses. The nature of the antigens recognized by the host has not been identified at any stage of tumor development. Here, we characterized the humoral immune response to viral antigens in cottontail and domestic rabbits at the papilloma stage, in domestic rabbits at the carcinoma stage, and in animals in which papillomas had regressed. Antibodies to linear epitopes were identified by Western blotting (immunoblotting) with bacterial fusion proteins, and evidence for recognition of conformational epitopes was obtained by immunoprecipitation. An immune response to the early proteins E1, E2, E6, and E7 was detected only in a fraction of the animals, and all animals were negative for E4 and E5. The response to E6 and E7 peaked around 7 months and then decreased, while that to E1 and E2 remained level after an initial raise. The antibody response to structural proteins was low at the papilloma stage, and antibodies to L1 recognized predominantly conformational epitopes. As papillomas progressed to carcinomas, there was a drastic increase in the response to L1 and L2, suggesting a change in interaction between virus-infected host cells and the host's immune system.